APLIKASI PAKAN PELET BUATAN UNTUK PENINGKATAN PRODUKTIVITAS BUDIDAYA IKAN AIR TAWAR - Yunaidi Yunaidi; Anugrah Perdana Rahmanta; Ari Wibowo (Universitas Ahmad Dahlan, Yogyakarta, 2019)
This activity aims to provide guidance, training, and mentoring to help resolve problems faced by partners, including high operational costs of fish farming because of the high cost of factory-made pellets, limited understanding and knowledge of fish farming techniques, and limited access to business capital in groups of freshwater fish farming in village of Jerukagung Srumbung Magelang. In this activity, the use of semi-intensive farming technology was introduced and the introduction of mixer and fish pellet feed making machines technology were able to produce pellets independently for groups of fish farmers. Semi-intensive system farming techniques are proven to be able to increase productivity at a low cost to replace the conventional methods that have been done so far. The service program was completed in eight months, divided into three stages consisting of competency enhancement, technology development, and partnership development. The use of semi-intensive farming technology by applying good pond water maintenance techniques, selecting the right seeds, and optimal feeding techniques has been shown to increase fish production. High feed costs during the enlargement process which can reach 75% of the total cost can be replaced using pellet feed has made by group using local raw materials that are easily available in the surrounding area or environment, so as to reduce feed costs by up to 25%.